Hanging Out And Purchase Decision - Dzamani, Muhammad Robbita; Muzakir, Mellisa (Universitas Negeri Yogyakarta, 2025)
This study investigates the effect of brand awareness, brand image, and brand ambassador on purchase decisions at Cafe Mental Tempe. Employing a quantitative survey design, the research collected primary data from 100 customers selected through purposive sampling. Data were obtained via a validated Likert-Scale questionnaire and analyzed using multiple linear regression to assess both simultaneous and partial influences of the independent variables purchase decision. Empirical results indicate that brand awareness, brand image, and brand ambassador each have a positive and statistically significant effect on customers’ purchase decisions. The simultaneous regression test confirms that the three variables jointly explain a meaningful proportion of variance in purchase intention, while the t-test shows that each predictor contributes significantly in partial analysis. These findings suggest that an integrated brand enhances consumer recognition, cultivating favorable perceptions, and deploying credible brand representatives. This study contributes to marketing practice by demonstrating that small to medium food outlets can strengthen sales performance through coordinated branding strategies. For future research, a longitudinal design and a larger, probabilistic sample are recommended to generalize findings across regions and examine the long-term effect of brand strategies on customer loyalty.